Properties and behavior of squeeze pressure on aluminum molybdenum DI-supplied composite - Arunkumar, S; Chandrasekaran, M; Vinod Kumar, T; Muthuraman, V (International Journal of Engineering and Technology, 2018)
To develop a metal matrix composite with lubricative properties with the help of various casting process and they are tested for their proper-ties. Casting machine is turned ON. Furnace temperature is set to 850o C. Preheater temperature is set to 180o C. Pathway temperature is set to 550o C. The furnace is allowed to get heated up. Once it gets heated upto 600o C, the A-Si alloy is dropped into the furnace. The alloy gets melted at around 800-850o C. Molybdenum di-sulphide fine powder is preheated and then mixed with the molten metal. Molybdenum di-sulphide is a reinforcement added and it is preheated to increase the wettability. Stainless steel stirrer is used to mix the alloy and graphite well. Stirrer is rotated between 200-300rpm.Once both the alloy and reinforcement gets mixed up into a single red hot molt, it is poured. The molt now leaves from the bottom of the furnace through the pathway. Pathway is maintained at 550o C to avoid solidification of molt in the path. Pathway carries the molt to a die, where it is poured. A squeeze pressure of 30 tonnes and 60 tonnes is given on the die using a piston. Die is split up and the mould is taken out from it. The die, furnace, pathway are coated with a layer of non-stick coating to avoid the sticking of alloy in the walls. The same process is repeated in stir casting, except that, pathway is not needed. The molten alloy is poured directly into the die without any pressure being applied. The die is split and the mould is taken. Coating is done before the next casting.Graphite powder and the Al-Si alloy materials are casted using squeeze casting process. Wear strength, tensile strength, flexural strength, impact strength and hardness test for the squeeze casted material is found out. The same materials are casted with the help of the stir casting process and they are compared with the squeeze cast material. Various testing process are to be carried out on the casted material and the results are compared.Â Â